2002
DOI: 10.1080/0003681021000021060
|View full text |Cite
|
Sign up to set email alerts
|

Some Conditions for the Nonexistence of Limit Cycles in a Predator-Prey System

Abstract: In this paper, we study the problem of the existence of limit cycles for a predator-prey system with a functional response. It is assumed that the functional response is positive, increasing, concave down, and its third derivative has a unique root. A necessary condition for the nonexistence of limit cycles is presented. Some conditions are given under which the necessary condition is also the sufficient condition for the nonexistence of limit cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Under some general conditions on the response function p(x), Moghadas [14] showed that (for the special case K = 1) system (1) has no cycle if and only if 2x…”
Section: Other Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under some general conditions on the response function p(x), Moghadas [14] showed that (for the special case K = 1) system (1) has no cycle if and only if 2x…”
Section: Other Modelsmentioning
confidence: 99%
“…A concrete counterexample was constructed in Hofbauer and So [6]. To different degrees Cheng et al [2], Kuang [11], Moghadas [14], and Xiao and Zhang [21] contain modifications of Hsu's result. But the sufficient conditions they proposed are difficult to satisfy and hard to verify, and the geometrical interpretation of their results is not clear.…”
Section: Cycles In Gause-type Predator-prey Systems 3623mentioning
confidence: 99%
See 1 more Smart Citation